Penggunaan Learning Management System di Pendidikan Tinggi Pada Masa Pandemi Covid-19: Model UTAUT - Iqbal Hanif Rohmatulloh; Jaka Nugraha (Universitas Negeri Surabaya, 2022)
Technological advances in the last 10 (ten) years have increased the use of mobile devices, and the availability of the internet has made online learning a trend, especially during the Coronavirus Disease (COVID-19) pandemic where learning activities are centered in each other's homes, so it is necessary Learning Management System (LMS) supporting online learning. The data analysis method used in this study is Structural Equation Modeling-Partial Least Square (SEM-PLS) with a total research sample of 165 respondents consisting of students from the S1 Office Administration Education study program who have used the Virtual Learning platform at the Universitas Negeri Surabaya (VINESA) during the COVID-19 pandemic. The results obtained in this study are Performance Expectancy has a significant positive effect on Behavioral Intention in accepting and using VINESA during the COVID-19 pandemic, Social Influence significantly positive effect on Behavioral Intention in accepting and using VINESA during the COVID-19 pandemic, Facilitating Condition does not have a significant positive effect on Behavioral Intention in accepting and using VINESA during the COVID-19 pandemic, Effort Expectancy has a significant positive effect on Behavioral Intention in accepting and using VINESA during the COVID-19 pandemic, and Behavioral Intention has a significant positive effect on Use Behavior in accepting and using VINESA during the COVID-19 pandemic.